2006
DOI: 10.1080/00288330.2006.9517414
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution ofPfiesteriaspp. (Pfiesteriaceae) in Tasman Bay and Canterbury, New Zealand (2002–03)

Abstract: The fish-killing heterotrophic dinoflagellate species Pfiesteria piscicida and P. shumwayae (also Pseudopfiesteria shumwayae)were present throughout New Zealand and were residents of Tasman Bay's well-flushed estuaries and Canterbury's brackish lakes, as determined by polymerase chain reaction-based detection assays. The two species occurred in a wide range of salinities and temperatures, although detection was restricted seasonally from spring through to autumn, except for one incidence in the shallow waters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Early distribution studies have reported that P. shumwayae has been detected on every continent, including multiple locations of the U.S., Australia and New Zealand, which imply that this species is cosmopolitan (Rublee et al, 2001Rhodes et al, 2002Rhodes et al, , 2006Bowers et al, 2006;Tango et al, 2006). However, the false positive PCR reactions with Australian genotypes of C. brodyi suggested that genetically related species had been misidentified as P. shumwayae and the geographic range of this species might have been overestimated in Australia and other counties.…”
Section: 2mentioning
confidence: 88%
See 2 more Smart Citations
“…Early distribution studies have reported that P. shumwayae has been detected on every continent, including multiple locations of the U.S., Australia and New Zealand, which imply that this species is cosmopolitan (Rublee et al, 2001Rhodes et al, 2002Rhodes et al, , 2006Bowers et al, 2006;Tango et al, 2006). However, the false positive PCR reactions with Australian genotypes of C. brodyi suggested that genetically related species had been misidentified as P. shumwayae and the geographic range of this species might have been overestimated in Australia and other counties.…”
Section: 2mentioning
confidence: 88%
“…Sequences of environmental clones (GenBank accession nos. DQ387443-9, DQ401157) amplified using P. shumwayae-selective primers showed a considerable divergence (4%) from P. shumwayae (Rhodes et al, 2006;Rublee et al, 2006), and those sequences did not match with Australian genotypes of C. brodyi or other related species indicating cross-reactivity with unknown species. These findings suggest that previous P. shumwayae identifications in Australian estuaries were most probably C. brodyi and not P. shumwayae.…”
Section: 2mentioning
confidence: 93%
See 1 more Smart Citation
“…The finding of C. brodyi in the Chapman River confirms that this species is widely distributed and commonly present in Australia. P. shumwayae has been detected previously on every continent by using molecular probes based on SSU rDNA, suggesting that P. shumwayae is a cosmopolitan species (4,28,29,30,31,32,33,39). In Australia, this species was detected in various locations in Queensland, South Australia, Victoria, Western Australia, and Tasmania (P. A. Rublee, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The P. shumwayae-specific primer set and the P. piscicida-specific primer-probe set were previously designed from mitochondrial cytochrome b gene (cob) (Zhang and Lin 2005) and from SSU rDNA (Bowers et al 2000), respectively ( Table 1). Specificity of these assays has been tested against other related species and has been confirmed by sequence analysis of PCR amplicons from natural waters (Bowers et al 2000;Zhang and Lin 2005;Rhodes et al 2006). Prior to use of both real-time PCR assays for Antarctic water samples, specificity was also tested with Australian genotypes of Cryptoperidiniopsis brodyi (CBWA12, CBSA4, CBHU1, CBDE1, and CBDE10) because these sequences were not available when these assays were developed.…”
Section: Methodsmentioning
confidence: 99%